Arabic Script on Christian Kings. Textile Inscriptions on Royal Garments from Norman Sicily - Dolezalek, Isabelle (Das Mittelalter. Perspektiven mediävistischer Forschung. Beihefte, 2017)
Isabelle Dolezalek is the recipient of the 2018 ICMA Annual Book Prize. Roger II's famous mantle and other royal garments from twelfth- and thirteenth-century Sicily prominently display Arabic inscriptions. While the phenomenon is highly unusual in the context of Latin Christian kingship, the use of inscriptions as a textile ornament was common and imbued with political functions in the Islamic courts of the medieval Mediterranean. This case study of the inscribed garments from Norman Sicily draws attention to the diverse functions of Arabic textile inscriptions using various contextual frames. Such a contextual approach not only highlights the specificities of the Norman textile inscriptions and emphasises the practical and political choices underlying their use at the Sicilian court, it also pinpoints the flaws of universalising approaches to transcultural ornamental in circulation in the medieval Mediterranean. This new perspective on the royal garments from Norman Sicily draws from a variety of disciplines, including Islamic and European art history, the history of textiles, epigraphy, legal history and historiography, and aims to challenge established notions of cultural and disciplinary boundaries.